2019
DOI: 10.34117/bjdv5n10-114
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors involved in retained placenta of dairy cows from family agriculture herds

Abstract: Risk factors involved in retained placenta of dairy cows from family agriculture herds Fatores de risco envolvidos na retenção de placenta de vacas leiteiras em rebanhos da agricultura familiar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…This study showed the same results that the incidence of retained placenta in dams with male calves was higher (23.12%) than in dams with female calves (17.85%) (Al-Yamani et al, 2021). However, the effect of calf sex is considered controversial for the incidence of retained placenta (Bernardi et al, 2019). This controversy might be due to different maternal factors of the male from female calves that are remains unclear.…”
Section: Characteristics Of Dams and Calvessupporting
confidence: 64%
“…This study showed the same results that the incidence of retained placenta in dams with male calves was higher (23.12%) than in dams with female calves (17.85%) (Al-Yamani et al, 2021). However, the effect of calf sex is considered controversial for the incidence of retained placenta (Bernardi et al, 2019). This controversy might be due to different maternal factors of the male from female calves that are remains unclear.…”
Section: Characteristics Of Dams and Calvessupporting
confidence: 64%